Carpogenic germinability of diverse Sclerotinia sclerotorium (Lib.) de Bary populations within the south-western Australian grain belt - Michael, Pippa; Lui, King-Yin; Thomson, Linda; Stefanova, Katia; Bennett, Sarita (American Phytopathological Society, 2020)
Sclerotinia stem rot, caused by the necrotrophic plant pathogen Sclerotinia sclerotorium (Lib.) de Bary, is a major disease of canola and pulses in Australia. Current disease management relies greatly on cultural and chemical means of control. Timing of fungicide applications remains a challenge, as efficacy is dependent on accurate prediction of ascospore release and presence on the plant. The aims of this study were to determine the optimal temperature for carpogenic germination of S. sclerotorium populations sampled from canola and lupin fields in south-western Australia and characterise diversity using mycelial compatibility groupings (MCGs). Sclerotia were collected from four diseased canola and one diseased lupin field from across south-western Australia. Forty sclerotia from each population were incubated at four alternating temperatures of 30/15°C, 20/15°C, 20/4°C and 15/4°C (12/12 hourly light/dark cycle) and assessed every 2-3 days for a 180-day period. MCG groupings for populations were characterised using 12 reference isolates. Results indicated the time to initial carpogenic germination decreased as diurnal temperature fluctuations decreased, with a fluctuation of 5°C (20/15°C) having the most rapid initial germination followed by 11°C (15/4°C) followed by 16°C (20/4°C). Optimal germination temperature for all five populations was 20/15°C, however population responses to other diurnal temperature regimes varied considerably. No germination was observed at 30/15°C. MCG results indicate extensive diversity within and between populations, with at least 40% of sclerotes within each population unable to be characterised. We suggest that this diversity has enabled S. sclerotorium populations to adapt to varying environmental conditions within south-western Australia.